2018
DOI: 10.2147/opth.s177933
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microvascular changes in the macular area of eyes with rhegmatogenous retinal detachment without macular involvement using swept-source optical coherence tomography angiography

Abstract: PurposeTo evaluate microvascular changes in the macular area of eyes with rhegmatogenous retinal detachment (RRD) without macular involvement (macula-on RRD) using swept-source optical coherence tomography angiography (SS-OCTA).Patients and methodsFive patients with macula-on RRD were eligible for analysis. All patients underwent SS-OCTA examination (Triton) for the macular area. The healthy fellow eyes were included as controls. The vessel density (VD) was calculated using binarization, and the foveal avascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
(15 reference statements)
6
23
1
Order By: Relevance
“…31 Tsen et al prospectively evaluated 28 eyes with mac-off RRD using OCT-A and reported VD to be significantly lower in the SCP and DCP in the RD eyes compared to the fellow eyes 32 while Yoshikawa et al investigated 5 eyes with mac-on RRD pre-operatively and reported parafoveal VD and FAZ to be not significantly different between the eyes with RRD and the fellow eye suggesting that the macular microvasculature remains intact. 30 In our study of 17 eyes with mac-off RD, we found a reduction of the VD in the DCP employing OCT-A. Furthermore, we report worse visual outcomes in eyes which had reduced VD in the deep capillary plexus compared with those that did not.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…31 Tsen et al prospectively evaluated 28 eyes with mac-off RRD using OCT-A and reported VD to be significantly lower in the SCP and DCP in the RD eyes compared to the fellow eyes 32 while Yoshikawa et al investigated 5 eyes with mac-on RRD pre-operatively and reported parafoveal VD and FAZ to be not significantly different between the eyes with RRD and the fellow eye suggesting that the macular microvasculature remains intact. 30 In our study of 17 eyes with mac-off RD, we found a reduction of the VD in the DCP employing OCT-A. Furthermore, we report worse visual outcomes in eyes which had reduced VD in the deep capillary plexus compared with those that did not.…”
Section: Discussionmentioning
confidence: 47%
“…It has been extensively investigated in macular degeneration, retinal vein occlusion, diabetic retinopathy, posterior uveitis and optic neuropathies. [22][23][24][25][26][27] Recently, few reports investigated OCT-A parameters after mac-on [28][29][30] or mac-off 28,29,31,32 RD repair including vascular density (VD) and FAZ area and correlated those with visual function. Building on those reports, we herein employed OCT-A to evaluate microvascular changes in the superficial (SCP) and deep capillary plexuses (DCP), choriocapillaris and the FAZ area and their correlation with final best corrected visual acuity (BCVA) in eyes after mac-off RRD repair using the fellow eyes as controls.…”
Section: Background and Objectivementioning
confidence: 99%
“…In this study, we investigated the vasculature parameters (VD, CCP flow area and FAZ) of the macular region in eyes successfully treated with PR for primary macula‐on and macula‐off RRD and assessed their correlation with functional and anatomical results. Previous studies have investigated the alterations in microvasculature structure after PPV for RRD repair; this is the first study using OCTA to evaluate and quantitate VD in superficial, deep retinal, and choroidal capillary plexuses after PR (Woo et al 2018; Yoshikawa et al 2018; Bonfiglio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although there have already been several reports that examined the FAZ area in various retinal diseases and glaucoma [11-13, 23, 24],the magnification effect was not always considered in the evaluation on the FAZ area. Linderman et al [14] reported that both axial length and refraction abnormality influence the measurement results due to the magnification effect.…”
Section: Discussionmentioning
confidence: 99%